Research status and development trend of extracorporeal membrane oxygenation based on bibliometrics - Guan, Cuizhong; Shen, Hua; Dong, Shiyong; Zhan, Yuhua; Yang, Jie; Zhang, Qiu; Wang, Rong (Frontiers in Cardiovascular Medicine, 2023)
Background Using bibliometric method to analyze the research status and development trend of extracorporeal membrane oxygenation (ECMO), we aim to provide clinicians, scientists, and stakeholders with the most up-to-date and comprehensive overview of ECMO research. Materials and methods Using Excel and VOSviewer, the literature on ECMO was systematically analyzed regarding publication trends, journal source, foundation, countries, institutions, core authors, research hotspots, and market distribution. Results There were five important time nodes in the research process of ECMO, including the success of the first ECMO operation, the establishment of ELSO, and the outbreak of influenza A/H1N1 and COVID-19. The R&D centers of ECMO were the United States, Germany, Japan, and Italy, and the attention to ECMO was gradually increasing in China. The products most used in the literature were from Maquet, Medtronic, and LivaNova. Medicine enterprises attached great importance to the funding of ECMO research. In recent years, the literature has mainly focused on the following aspects: the treatment of ARDS, the prevention of coagulation system-related complications, the application in neonatal and pediatric patients, mechanical circulatory support for cardiogenic shock, and ECPR and ECMO during the COVID-19 pandemic. Conclusion The frequent epidemic occurrence of viral pneumonia and the technical advancement of ECMO in recent years have caused an increase in clinical applications. The hot spots of ECMO research are shown in the treatment of ARDS, mechanical circulatory support for cardiogenic shock, and the application during the COVID-19 pandemic.